The Effect of Providing Fermented Pineapple Peel in The Ration on The Performance of Peking Ducks - N. Haiza; K. Sumadi; N. W. Siti; Bulkaini Bulkaini; Djoko Kisworo; Fahrullah Fahrullah (Jurnal Biologi Tropis, 2023)
This research aims to determine the performance of male Peking ducks given rations containing fermented pineapple peel at the Teaching Farm, Faculty of Animal Science, University of Mataram. The research was carried out for 10 weeks using a Completely Randomized Design, consisting of 6 treatments and 5 replications. Each replication used 8 male Peking ducks aged two weeks so that the number of ducks used was 240. The treatments were P0 = control, P1 = 5% fermented pineapple peel, P2 = 10% fermented pineapple peel, P3 = 15% fermented pineapple peel, P4 = 20% fermented pineapple peel and P5 = 25% fermented pineapple peel. The research variables were: final body weight, body weight gain, ration consumption, Feed Converation Ratio, percentage of carcass and non-carcass analyzed using analysis of variance. The results of the study showed that giving fermented pineapple peel up to a level of 25% had a significant effect (P<0.05) on final body weight, body weight gain and feed consumption, but was not significantly different (P>0.05) on the feed conversion ratio, carcass percentage, small intestine length, small intestine percentage, liver percentage, and leg percentage. Conclusion: Providing fermented pineapple peel to a level of 10% increased final weight, body weight gain, feed consumption, head and neck percentage but reduced heart percentage and gizzard percentage. Feed conversion ratio, carcass percentage, small intestine length, small intestine percentage, liver percentage, and leg percentage were relatively similar between treatments.